Plasma Indoleamine 2,3-Dioxygenase Activity Is Associated With the Size of the Human Immunodeficiency Virus Reservoir in Patients Receiving Antiretroviral Therapy - Jun Chen; Jingna Xun; Junyang Yang; Yongjia Ji; Li Liu; Tangkai Qi; Zhenyan Wang; Renfang Zhang; Yinzhong Shen; Rosalie Ponte; Vikram Mehraj; Jean‐Pierre Routy; et al. (2018)
Indoleamine 2,3-dioxygenase (IDO) is an immunoregulatory enzyme that metabolizes tryptophan to immunosuppressive kynurenines. We investigated whether IDO activity is associated with the size of HIV reservoir.Total human immunodeficiency virus (HIV) DNA in peripheral blood mononuclear cells (PBMCs) from 127 HIV-infected patients receiving antiretroviral therapy (ART) was quantified. Tryptophan and kynurenine concentrations, as well as microbial translocation markers, were measured in plasma samples. T-cell activation and exhaustion in PBMCs were assessed by flow cytometry.Elevated IDO activity prior to ART correlated with on-ART HIV DNA (r = 0.35, P = .004), but was not associated with pre-ART HIV DNA. A median duration of 15 months of ART significantly decreased IDO activity; however, these levels were still higher than those observed in HIV-uninfected controls. Among treated participants, IDO activity positively correlated with their concurrent HIV DNA (r = 0.36, P < .0001). Multivariate model showed an independent association of pre-ART CD4/CD8 ratio (adjusted odds ratio [aOR], 0.75 per 0.1 increase [95% confidence interval CI, .62-.91]) and on-ART IDO activity (aOR, 1.09 per nM/μM increase [95% CI, 1.04-1.14]) with higher levels of HIV DNA on-ART. A lack of association of the microbial translocation markers was observed with the size of HIV reservoir. HIV DNA positively correlated with the proportions of activated CD4 T and CD8 T cells and exhausted CD4 T cells.We observed a positive correlation between IDO activity and total HIV DNA in blood, highlighting the important role of immunometabolic aberrations in HIV persistence.